Young Ischemic Stroke in South Asia: A review - Ojha, Rajeev; Huang, Dongya; An, Hedi; Zuo, Lian; Zhu, Wenxia (Journal of Advances in Internal Medicine, 2013)
Stroke in young adults may have early impact on quality of life in survivors. Uncontrolled stroke risk factors, lack of treatment facilities and a dense population has made its special significance in South Asia. The main aim of this study is to evaluate incidence, risk factors, etiology and clinical characteristics of young ischemic stroke in South Asia. Incidence of young stroke is more common in South Asian countries than developed western countries and has higher prevalence in rural areas. Traditional risk factors, such as hypertension, smoking, hyperlipidemia and diabetes are associated with majority of cases. Cardioembolism and undetermined etiology contribute to a large proportion of stroke etiology. Appropriate stepwise investigations are suggested to diagnose stroke of other determined etiology. Regular intake of drugs to control risk factors, cessation of smoking, and promote physical activity is suggested to reduce the burden of young stroke. Journal of Advances in Internal Medicine 2013;02(01):27-33 DOI: http://dx.doi.org/10.3126/jaim.v2i1.7636